KAJIAN TINGKAT KEBERLANJUTAN PEMBANGUNAN WILAYAH DI DAERAH ISTIMEWA YOGYAKARTA TAHUN 2000-2010 - , APIP PRIADI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Nowdays, the development focuses on economic growth and ignore environmental damage. It is occures in Daerah Istimewa Yogyakarta (DIY) where regencies and cities have positive growth in economic but decrease in environmental. One of the solutions that might be solve this issue is sustainable development. It integrates economic, social, and environmental development. The aims of this research are to analyze economic, social, and environmental development and to fnd out the status of sustainability each regencies and cities in 2000-2010. This research applies descriptive quantitative analysis methode and uses scalling analysis technique and cassification. This methode to analyse 25 sustainability development indicators. Those 25 indicators are divided 3 groups